SABER - School Health : Preliminary Assessment of School Health Policies in the Caribbean Community - Ebenezer, Roshini (World Bank, Washington, DC, 2015)
This report presents the findings of the 2012 pilot assessment of the school health policies for the following Caribbean community (CARICOM) countries: Dominica, Grenada, Guyana, St. Lucia, Barbados, and St. Vincent and the Grenadines. The objective of this exercise is to help countries to identify the strengths and weaknesses in their school health policy frameworks, with the understanding that sound a policy framework is a critical component of effective school health programming. The result is a preliminary report on the status of development of the school health policy framework in the six countries. Section one gives introduction. Section two briefly discusses the importance of school health programs in contributing to education sector goals and the development of international consensus on the basic building blocks of effective school health programs. Section three discusses the conceptual framework of system assessment and benchmarking for education results (SABER) - school health, and introduces the components of the SABER - school health framework and scoring system. Section four provides the context for and objectives of this assessment as well the methodology used for data collection. Section five presents the results for the six countries: first by individual country and then as a comparative analysis across each of four policy domains.